Pengaruh Media Pendingin pada Perlakuan Panas T6 terhadap Kekuatan Tarik dan Struktur Mikro Komposit Al6061-Pasir pantai - Hafidh Rawi Mufti; Hammar Ilham Akbar; Eko Surojo; Wibowo Wibowo; Teguh Triyono; Sukmaji Indro Cahyono; Nurul Muhayat; Triyono Triyono (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
Al6061-sea sand composite was manufactured using the stir casting method and its mechanical properties were improved by heat treatment. The T6 heat treatment used to improve the mechanical properties of the composite consists of the following processes: solution heat treatment, quenching, and artificial aging. The solution heat treatment process was carried out at a temperature of 540oC for 6 hours. The quenching process was carried out with different quenching agents (water, oil, and 10% brine). The difference in quenching agents resulted in different cooling rates. After quenching, an artificial aging process was carried out at a temperature of 200 oC for 4 hours. The difference in cooling rate affects the hardness and tensile strength of the specimen. The high cooling rate results in an increase in the tensile strength of the specimen. This is due to the increase in cooling speed, the Mg2Si precipitates formed are smaller in size and located in the grains. The highest tensile strength of specimen (206.67 MPa) is obtained by using brine quenching agent.